Implementasi Radio Frequency Identification (RFID) Untuk Kartu Pasien Berbasis Data Digital - Evrita Lusiana Utari; Irawadi Buyung; Agus Qomaruddin Munir (Jurnal Teknologi, 2022)
Today's technological developments have largely replaced conventional ones. One example is the RFID system. Patient Card is an identification in the form of patient data documents in conventional hospitals. Therefore, with this RFID system, it can contain a security control system both in terms of administration and information technology based on a database in the Hospital. The data is stored in the Patient Card based on digital data. Utilization of digital data-based patient cards to speed up patient services in the registration process during treatment, and reduce queue times when the data identification process is carried out by the patient registration department, as well as the efficiency of human resources. The process of designing tools by initializing the use of tool components. The data processing is carried out by Arduino Nano to read RFID and serial communication to communicate with Arduino UNO as a graphic LCD display. The Arduino Uno processor used detects the card. With the validation of the card, the patient can continue the examination process to the desired poly and exit in the form of a printed queue number according to the destination poly.